Memahami Konteks Sosio-Historis Turunnya Wahyu: Analisis terhadap Ayat-Ayat Makkiyah dan Madaniyah dalam Al-Qur’an - Azzah Fadiyah Nurfadhilah Fahman; Muh. Mukhlis Rahman (PT. PENERBIT TIGA MUTIARA, 2024)
This study aims to describe the errors made by students in solving story problems using Newman’s procedure analysis and in terms of students’ learning styles. The type of research used is descriptive qualitative research. The subjects of this study were students of class VIIIع with a total of 23 students and selected using purposive sampling as many as 9 students based on visual, auditory and kinetic learning styles. The data collection technique in this study used a learning style questionnaire test which was tested with 23 students of class VIIIع, a story problem test on the system of linear equations of two variables which was tested with 9 students who were selected based on learning style groups and interviews. Based on the results of the study there were 10 students with visual learning styles, 9 students with auditory learning styles and 4 students with kinaesthetic learning styles. Obtained from the research data are: a) Students with visual learning styles made errors based on Newman’s procedure in understanding the problem and writing the final answer; b) Students with auditory learning styles made errors based on Newman’s procedure on understanding the problem, transformation, process skills and writing the final answer, c) Students with kinaesthetic learning styles made errors based on Newman’s procedure on understanding the problem, transformation, process skills and writing the final answer.